Exploring Readiness for Implementing Citizen-Friendly Public Service Policy in Makassar Civil Registry Office - Fitria Utami; Hamrun Hamrun; Muhammad Amril Pratama Putra (Smart Society, 2025)
Citizen-friendly public service has emerged as a crucial aspect of modern governance, emphasizing inclusivity, empathy, and efficiency. However, the readiness to implement such policies at the local government level, particularly within civil registration services, remains underexplored. This study aims to examine institutional, procedural, and human resource readiness for implementing a citizen-friendly public service policy at the Civil Registry Office of Makassar City. Using a qualitative descriptive approach, data were collected through in-depth interviews, non-participant observations, and document analysis. Findings reveal that while digital transformation initiatives such as the 'Kucata’ki' application have improved administrative efficiency, significant challenges persist in digital literacy, communication ethics, and public awareness. The study concludes that readiness for implementing citizen-friendly services requires not only technological preparation but also ethical, procedural, and collaborative foundations to ensure inclusivity and trust in public service delivery. The results provide valuable insights for developing a comprehensive implementation strategy for inclusive and human-centered public services in Indonesia.